Answer
The function \( f(x) = -x^{3} + 6x^{2} - 9x + 4 \) can be factored as \( f(x) = - (x - 1)^2 (x - 4) \). It has roots at \( x = 1 \) (with multiplicity 2) and \( x = 4 \). There is a local minimum at \( (1, 0) \) and a local maximum at \( (3, 4) \). As \( x \) approaches infinity, \( f(x) \) goes to negative infinity, and as \( x \) approaches negative infinity, \( f(x) \) goes to positive infinity.
Solution
Certainly! Let's analyze the function provided:
\[
f(x) = -x^{3} + 6x^{2} - 9x + 4
\]
This analysis will cover **factoring the polynomial**, **finding its roots**, **determining critical points**, and **discussing the overall behavior of the function**.
---
### 1. **Factoring the Polynomial**
First, factor out \(-1\) to simplify the expression:
\[
f(x) = -\left(x^{3} - 6x^{2} + 9x - 4\right)
\]
Now, let's factor the cubic polynomial inside the parentheses.
**a. Finding Rational Roots:**
The **Rational Root Theorem** suggests that any possible rational roots \( p/q \) are factors of the constant term divided by factors of the leading coefficient. For the polynomial \( x^{3} - 6x^{2} + 9x - 4 \):
- **Possible Rational Roots:** \( \pm1, \pm2, \pm4 \)
**b. Testing Possible Roots:**
Let's test \( x = 1 \):
\[
1^{3} - 6(1)^{2} + 9(1) - 4 = 1 - 6 + 9 - 4 = 0
\]
Since \( f(1) = 0 \), \( x = 1 \) is a root.
**c. Polynomial Division:**
Using **synthetic division** to divide the polynomial by \( (x - 1) \):
\[
\begin{array}{r|rrrr}
1 & 1 & -6 & 9 & -4 \\
\hline
& 1 & -5 & 4 & 0 \\
\end{array}
\]
This yields:
\[
x^{3} - 6x^{2} + 9x - 4 = (x - 1)(x^{2} - 5x + 4)
\]
**d. Factoring Further:**
Factor the quadratic \( x^{2} - 5x + 4 \):
\[
x^{2} - 5x + 4 = (x - 1)(x - 4)
\]
**e. Complete Factorization:**
Putting it all together:
\[
f(x) = - (x - 1)^{2}(x - 4)
\]
---
### 2. **Finding the Roots of \( f(x) \)**
Set \( f(x) = 0 \):
\[
- (x - 1)^{2}(x - 4) = 0
\]
**Solutions:**
- \( (x - 1)^{2} = 0 \) ⟹ \( x = 1 \) (double root)
- \( x - 4 = 0 \) ⟹ \( x = 4 \)
**Roots:**
\[
x = 1 \quad (\text{with multiplicity } 2), \quad x = 4
\]
---
### 3. **Determining Critical Points**
To find the critical points, compute the first derivative \( f'(x) \) and set it to zero.
**a. First Derivative:**
\[
f'(x) = \frac{d}{dx}\left[-x^{3} + 6x^{2} - 9x + 4\right] = -3x^{2} + 12x - 9
\]
Factor the derivative:
\[
f'(x) = -3(x^{2} - 4x + 3) = -3(x - 1)(x - 3)
\]
**b. Setting \( f'(x) = 0 \):**
\[
-3(x - 1)(x - 3) = 0
\]
**Solutions:**
- \( x = 1 \)
- \( x = 3 \)
**c. Identifying Local Extrema Using the Second Derivative:**
Compute the second derivative \( f''(x) \):
\[
f''(x) = \frac{d}{dx}[-3x^{2} + 12x - 9] = -6x + 12
\]
**Evaluate at Critical Points:**
- **At \( x = 1 \):**
\[
f''(1) = -6(1) + 12 = 6 > 0 \quad \text{(Local Minimum)}
\]
- **At \( x = 3 \):**
\[
f''(3) = -6(3) + 12 = -6 < 0 \quad \text{(Local Maximum)}
\]
**d. Function Values at Critical Points:**
- **At \( x = 1 \):**
\[
f(1) = -1 + 6 - 9 + 4 = 0
\]
- **At \( x = 3 \):**
\[
f(3) = -27 + 54 - 27 + 4 = 4
\]
**Critical Points:**
- **Local Minimum:** \( (1, 0) \)
- **Local Maximum:** \( (3, 4) \)
---
### 4. **Behavior of the Function**
- **End Behavior:**
- As \( x \to \infty \), \( f(x) \to -\infty \) (since the leading term is \(-x^{3}\)).
- As \( x \to -\infty \), \( f(x) \to \infty \).
- **Graph Characteristics:**
- **Roots:** \((1, 0)\) with multiplicity 2 (the graph touches the x-axis and turns around) and \((4, 0)\).
- **Local Extrema:** A local minimum at \( (1, 0) \) and a local maximum at \( (3, 4) \).
- **Shape:** The graph has the general shape of a downward-opening cubic function, intersecting the x-axis at the specified roots and turning at the critical points.
---
### 5. **Summary**
- **Factorized Form:**
\[
f(x) = - (x - 1)^{2}(x - 4)
\]
- **Roots:**
\[
x = 1 \quad (\text{double root}), \quad x = 4
\]
- **Critical Points:**
- Local Minimum at \( (1, 0) \)
- Local Maximum at \( (3, 4) \)
- **End Behavior:**
- \( f(x) \to -\infty \) as \( x \to \infty \)
- \( f(x) \to \infty \) as \( x \to -\infty \)
This comprehensive analysis should provide a clear understanding of the function \( f(x) = -x^{3} + 6x^{2} - 9x + 4 \).
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution